2012
DOI: 10.3390/molecules17032675
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Phenolic Amides from Celtis africana

Abstract: Nine compounds have been isolated for the first time from Celtis africana, namely trans-N-coumaroyltyramine (1), trans-N-feruloyltyramine (2), trans-N-caffeoyltyramine (3), lauric acid (4), oleic acid (5), palmitic acid (6), lupeol (7), β-sitosterol (8) and oleanolic acid (9), respectively. Their structures have been elucidated by different spectroscopic techniques. The isolated compounds were screened for their antioxidant, anti-inflammatory and acetylcholinestrease enzyme inhibitory activities. Compounds 1-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 11 publications
1
51
0
Order By: Relevance
“…The known compounds ( 2 – 7 ) were identified, through comparison of their spectroscopic and physical properties with literature values, as the sesquiterpene (−)-guaiol ( 2 ) [ 18 ], the aporphine alkaloid (+)-isocorydine ( 3 ) [ 19 ], the azafluorenones cyathocaline ( 4 ) [ 20 ], and isoursoline ( 5 ) [ 21 ] and the cinnamoyl tyramides N - trans -coumaroyltyramine ( 6 ) [ 22 ] and N - trans -feruloyltyramine ( 7 ) [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The known compounds ( 2 – 7 ) were identified, through comparison of their spectroscopic and physical properties with literature values, as the sesquiterpene (−)-guaiol ( 2 ) [ 18 ], the aporphine alkaloid (+)-isocorydine ( 3 ) [ 19 ], the azafluorenones cyathocaline ( 4 ) [ 20 ], and isoursoline ( 5 ) [ 21 ] and the cinnamoyl tyramides N - trans -coumaroyltyramine ( 6 ) [ 22 ] and N - trans -feruloyltyramine ( 7 ) [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…30 On the basis of our results and those published in previous reports, phenolic amide derivatives isolated from T. terrestris could be potential candidates for development as an anti-inflammatory agent that exerts its therapeutic effects through inhibition of NO production.…”
Section: -15mentioning
confidence: 51%
“…N-trans-ρ-caffeoyl tyramine (CT) is one of the compounds isolated from T. terrestris (7). A previous study reported that CT acts as an antioxidant and moderately inhibits acetylcholinesterase in vitro and in vivo (8). However, the anti-inflammatory effects of CT have not yet been completely elucidated.…”
Section: Introductionmentioning
confidence: 99%